Developmental relations between sympathy, moral emotion attributions, moral reasoning, and social justice values from childhood to early adolescence. Issue 7 (6th September 2014) - Daniel, Ella; Dys, Sebastian P.; Buchmann, Marlis; Malti, Tina
ABSTRACT: This study examined the development of sympathy, moral emotion attributions (MEA), moral reasoning, and social justice values in a representative sample of Swiss children ( N  = 1273) at 6 years of age (Time 1), 9 years of age (Time 2), and 12 years of age (Time 3). Cross‐lagged panel analyses revealed that sympathy predicted subsequent increases in MEA and moral reasoning, but not vice versa. In addition, sympathy and moral reasoning at 6 and 9 years of age were associated with social justice values at 12 years of age. The results point to increased integration of affect and cognition in children's morality from middle childhood to early adolescence, as well as to the role of moral development in the emergence of social justice values.